Dificultades en la comprensión de la lectura con los niños de la Escuela 30 de Octubre - Tutillo Cholango, Guadalupe Esther (1999)
Introduction. Communication Pingulmi Santa Marianita of demographic and social and historical context. The oral and reading societies. Conclusions. Recommendations. Bibliography. Annexes.